Explantátová kultura Trifolium pratense L - Kasparová, M; Siatka, T; Spilková, J; Dusek, J (Ceska a Slovenska farmacie, 2006)
The red cloverl seems to be a prospective source of flavonoids and isoflavonoids with phytoestrogenic activity. Young seedlings of four different varieties of Trifolium pratense L. were employed to derive callus and suspension cultures. The optimal medium for cultivation is Gamborg's cultivating medium with an addition of 2 mg x l(-1) of 2,4-dichlorphenoxyacetic acid and 2 mg x l(-1) of 6-benzylaminopurine. On the basis of growth and production characteristics, subcultivating intervals of 29 to 43 days in callus culture and 16 to 23 days in suspension culture were determined. TLC and HPLC revealed that the explant culture of Trifolium pratense L. contains the isoflavonoid formononetin.
Keywords: flavonoidy; Flavonoids; kultivační techniky; Trifolium; Culture Techniques